Analysis of Pedagogical Content Knowledge (PCK) Topic Specific PCK Model for Chemistry Teachers at the Vocational School of Semarang in Stoichiometry - Aziz, Faishal; Haryani, Sri; Sumarti, Sri Susilogati (Universitas Negeri Semarang, 2020)
Pedagogical Content Knowledge (PCK) is an integration between content knowledge (CK) and pedagogical knowledge (PK) owned by teachers as a way to improve student learning and will develop over time and experience. PCK is not only emphasized on CK but with PK and balanced with teaching experience so that the knowledge and experience can be integrated. The purpose of this study was to analyze the ability of PK, CK, and PCK chemistry teachers at the Vocational School of Semarang. This research is a descriptive study to describe PCK chemistry teacher. The subjects of this study were chemistry teachers gathered in the MGMP Kimia SMK Semarang. The data are in the form of content and pedagogical knowledge test and TSPCK instruments. The PCK teacher's ability was obtained by analyzing the TSPCK instrument. Based on the analysis shows: (1) the teacher has a good PK value (76%); (2) the teacher has an score of CK very good (82%); and (3) the ability of PCK teachers, there are 2 teachers in the examplary category, 17 teachers in the developing category, and 3 teachers in the basic category. Teachers who have content or pedagogics knowledge or both are not guaranteed to produce effective learning.